Przesłanki wdrażania zalążków systemu informacji o terenie w Królestwie Polskim - Czochański, Marian (Wydawnictwo Politechniki Łódzkiej, 2010)
W opracowaniu zwrócono uwagę na uwarunkowania techniczno-prawne zawarte w przepisach administracyjnych Królestwa Polskiego, tworzących przesłanki do wdrażania zalążków systemu informacji o terenie.

The article drew attention of the technical and legal conditions contained in the administrative Polish Kingdom, creating conditions for the construction of a land information system.
Implementation of the incipient conditions for land information system in the Polish Kingdom